Information Warfare : Forging Communication Strategies for Twenty-first Century Operational Environments - Farwell, James P. (Book collections on Project MUSE., 2020)
Information Warfare recognizes that a communication strategy is an intrinsic component of a national strategy. Farwell builds on the foundation laid by historical and contemporary thinkers who recognized the need to forge a communication strategy to conduct effective information warfare. The author defines a communication/information warfare strategy that is persuasive and credible. He distills key factors to frame the strategic thinking for information warfare. The book is innovatively organized in two parts: First, Farwell delivers a concise treatise about the key steps for a communication strategy. It includes historical and current examples that offer deep insights. Deference is made to the military concept of operational art. The examples illustrate the environment, the problem to be addressed, and the approach to be used. This instructional section is amply footnoted to provide tremendous depth. Second, an easy-to-use workbook employs a step-by-step methodology with questions for the reader to address in creating and evaluating their own communication strategies"--